Sulfonamide-substituted iron phthalocyanine: design, solubility range, stability and oxidation of olefins - Isci, Umit; Caner, Celal; Zorlu, Yunus; Gürek, Ayşe Gül; Dumoulin, Fabienne; Ahsen, Vefa (Royal Soc Chemistry, 2014)
4-tert-Butylbenzenesulfonamide was used as a substituent of tetra peripherally substituted Fe(II) phthalocyanine, taking into account several parameters crucial for the design of potential oxidation catalysts such as solubility and stability. The resulting phthalocyanine exhibits a remarkable stability under oxidative conditions. The main product of the oxidation of cyclohexene using H2O2 as the oxidant is the allylic ketone, 2-cyclohexen-1-one. Styrene oxidation led mainly to the formation of benzaldehyde.
Keywords: Catalytic-Activity; Homogeneous Solution; Hydrogen-Peroxide; Allylic Oxidation; Cyclohexene; Porphyrins; Benzene; Methane